Development and validation of a training module on the use of acetic acid for the detection of Barrett’s neoplasia - Chedgy, Fergus J. Q.; Kandiah, Kesavan; Barr, Hugh; De Caestecker, John; Dwerryhouse, Simon; Eross, Balint; Gordon, Charles; Green, Susi; Li, Andy; Brown, James; Longcroft-Wheaton, Gaius; Bhandari, Pradeep (Endoscopy, 2017)
Background and study aims Acetic acid chromoendoscopy (AAC) enhances the ability to correctly identify Barrett’s neoplasia, and is increasingly used by both expert and nonexpert endoscopists. Despite its increasing use, there is no validated training strategy to achieve competence. The aims of our study were to develop a validated training tool in AAC-assisted lesion recognition, to assess endoscopists’ baseline knowledge of AAC-assisted lesion recognition, and to evaluate the efficacy and impact of this training tool.Methods A validated assessment of 40 images and 20 videos was developed. A total of 13 endoscopists with experience of Barrett’s endoscopy but no formal training in AAC were recruited to the study. Participants underwent: baseline assessment 1, online training, assessment 2, interactive seminar, assessment 3.Results Baseline assessment demonstrated a sensitivity of 83 % and a negative predictive value (NPV) of 83 %. The online training intervention significantly improved sensitivity to 95 % and NPV to 94 % (P < 0.01). Further improvement was seen after a 1-day interactive seminar including live cases, with sensitivity increasing to 98 % and NPV to 97 %. Conclusions The data demonstrate the need for training in AAC-assisted lesion recognition as baseline performance, even by Barrett’s experts, was poor. The online training and testing tool for AAC for Barrett’s neoplasia was successfully developed and validated. The training intervention improved performance of endoscopists to meet ASGE PIVI standards. The training tool increases the endoscopist’s degree of confidence in the use of AAC. The training tool also leads to shift in attitudes of endoscopists from Seattle protocol towards AAC-guided biopsy protocol for Barrett’s surveillance.